PECULIARITIES OF THE DEVELOPMENT OF INDIVIDUAL PROGRAMS OF PHYSICAL THERAPY FOR SYMPTOMATIC EPILEPSY IN CHILDREN - Kotenko, O. Yu. (Rehabilitation and Recreation, 2022)
In this robot, the leading causes of epilepsy in children, the classification of epilepsy according to ICC 10, which is typical for symptomatic epilepsy, are considered. Meta follow up. Theoretically, it is possible to apply the inclusion of specific features of kinesiotherapy, sensory therapy in a complex program of physical therapy for symptomatic epilepsy in children. Material and methods of follow-up: theoretical analysis of special medical literature, informational sources and background data, clinical and instrumental methods of follow-up (anamnesis, obstezhennya). The relevance of this is explained by the fact that the incidence of epilepsy in children is between 4.7–5.9 per 9 thousand children. The number of illnesses has increased in cases where epileptic attacks are blamed on children (children with cerebral palsy, autism spectrum disorder, meningitis, viral encephalitis). Disability due to epilepsy may be 4.5–5.0 per 9 thousand children [1]. Of the main material of Epilepsy is the breakdown of cerebral activity, characteristic of epilepsy is the scaling up to the vindication of epileptic attacks, and cognitive, psychological, social, functional impairments in the aftermath of persistent epilepsy attacks. Reference HIC -10 – epilepsy (G40) is classified into localized – focal, partial, idiopathic epilepsy, epileptic syndromes with attacks with focal cob (G40); localized – focal, partial, symptomatic epilepsy, epileptic syndromes with simple partial attacks (G40.1); localized – focal, partial, epileptic syndromes with complex partial attacks (G40.2); generalized idiopathic epilepsy and epileptic syndromes (G40.3); especially epileptic syndromes (G40.5); small attacks unspecified (G40.6); epilepsy, unspecified (G40.9); cognitive and mnestic disorders due to epilepsy (F02.803); mental disorders due to dysfunction and damage to the brain (F05.12) [4].